Trust in interaction studies - Muntigl, Peter; Scarvaglieri, Claudio; De Wilde, July; Bührig, Kristin; Wamprechtshammer, Anna (Frontiers in Communication, 2024)
Trust is argued to be essential in fostering cooperative communication, whereas a lack of trust is seen as detrimental to these aims. Over the years, there has been a slow but steady stream of research that has aimed to shed light on how trust is accomplished or broken down through discursive-interactional practices. In this mini review, we examine existing studies that take trust as a topic of investigation using micro-analytic, interactional methods, in order to provide readers with an up-to-date overview on new developments in this important field of research. From this review, we conclude that there exist two different, yet complementary, views on trust: Trust as an interactional principle and trust as a discursively accomplished phenomenon. We not only summarize important discursive work that provides a unique lens on how trust may be established and maintained through verbal and nonverbal resources, but also suggest some of the challenges interactional trust research still faces and some important areas for further investigation in which trust is a major concern.